2000
DOI: 10.1016/s0378-1097(00)00444-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipoteichoic acid on the uptake of Streptococcus pyogenes by HEp-2 cells

Abstract: Lipoteichoic acid (LTA) is thought to play a role in the interactions between Streptococcus pyogenes and host cells. We have examined the effect of exogenous LTA on the adherence and entry of S. pyogenes JRS4 strain into HEp-2 epithelial cells. LTA markedly inhibited bacterial entry in a concentration-dependent manner, up to 250 Wg ml 31 . In contrast, LTA had only a slight inhibitory effect on adherence. LTA also inhibited the entry but not adherence of Salmonella typhimurium strain into HEp-2 cells. Binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…LTA has been shown to play a role in GAS epithelial cell attachment and uptake (3,44). To assess the potential contribution of the D-alanyl modification of teichoic acids to these processes, we compared interactions of the WT and the ⌬dltA mutant with cultured monolayers of human pharyngeal epithelial cell line Hep-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LTA has been shown to play a role in GAS epithelial cell attachment and uptake (3,44). To assess the potential contribution of the D-alanyl modification of teichoic acids to these processes, we compared interactions of the WT and the ⌬dltA mutant with cultured monolayers of human pharyngeal epithelial cell line Hep-2.…”
Section: Resultsmentioning
confidence: 99%
“…LTA may be involved in processes such as the control of cell shape, autolytic enzyme activity, and maintenance of cation homeostasis (32). In GAS, LTA contributes to pharyngeal epithelial cell attachment (3,44). Classical biochemical and enzymologic studies indicated that GAS could incorporate D-alanine into its membrane-bound LTA through a two-step process involving a D-alanine-activating enzyme and D-alanine-D-alanyl carrier protein ligase (5).…”
mentioning
confidence: 99%
“…Growth of GAS in the presence of penicillin, which promotes the excretion of LTA, diminished their ability to adhere to epithelial cells (3). In studies of S. pyogenes internalization by epithelial cells (HEp-2), it was found that exogenous LTA inhibited entry of the bacterium into these cells (437). Entry is dependent on the initial LTA-mediated adhesion, and so the unique role of LTA in virulence would appear to be defined in GAS.…”
Section: Role In Virulencementioning
confidence: 99%
“…A recent report showed that free LTA specifically blocks intracellular invasion of Hep2 pharyngeal epithelial cells by S. pyogenes without affecting overall cellular adherence (44). In vivo, topical administration of LTA has also been shown to be effective in blocking vaginal colonization of pregnant mice by GBS (45).…”
Section: Figurementioning
confidence: 99%